An Improvement of UMP‐BP Decoding Algorithm Using the Minimum Mean Square Error Linear Estimator - Kim, Namshik; Kim, Jaebum; Park, Hyuncheol; Suh, Seung‐Bum (ETRI journal, 2004)
In this paper, we propose the modified uniformly most powerful (UMP) belief‐propagation (BP)‐based decoding algorithm which utilizes multiplicative and additive factors to diminish the errors introduced by the approximation of the soft values given by a previously proposed UMP BP‐based algorithm. This modified UMP BP‐based algorithm shows better performance than that of the normalized UMP BP‐based algorithm, i.e., it has an error performance closer to BP than that of the normalized UMP BP‐based algorithm on the additive white Gaussian noise channel for low density parity check codes. Also, this algorithm has the same complexity in its implementation as the normalized UMP BP‐based algorithm.